(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article analyzes the ideas of the famous Iranian philosopher Shihabuddin al- Suhrawardi . It is shown that the philosopher was able to carry out a deep synthesis between the sensible and intelligent, intuitive and logical. The traditional binary opposition of “mind-heart”, “science-spirituality” notions is shown in his work as lacking the necessary profundity to understand the reality. One of the first in the Islamic world, he carries out criticism of the ideas of the Peripatetic and neo-Platonism schools and depicts that these schools of philosophy are unable to achieve a deep understanding of the essence of things. At the same time he was trying to revive the philosophical wisdom of ancient Persia, being sure that the principles of the Islamic culture will allow him to understand the philosophical foundations on which all the previous religions of the world were originally built, but which were then deformed by ill-wills of people. That is why the ancient culture and the ancient Persian beliefs were easily incorporated by him into the intellectual corpus of the Islamic world, which all of the mankind – as he thought – must perceive as universal by its nature and its logical and persuasive structure. Thus, he was one of the first in the history of philosophy to put forward the thesis of «philosophia perennius» – «eternal philosophy», thereby laying out the groundwork for the emergence of philosophy of renowned Iranian thinkers such as Mulla Sadra. Keywords:, sufism, man, spiritual values, culture, philosophy, being, existence intellect.